Virtual lesions of the IFG abolish response facilitation for biological and non-biological cues - Newman-Norlund, Roger D.; Ondobaka, Sasha; Van Schie, Hein T.; Van Elswijk, Gijs; Bekkering, Harold (Frontiers in Behavioral Neuroscience, 2010)
Humans are faster to perform a given action following observation of that same action. Converging evidence suggests that the human mirror neuron system (MNS) plays an important role in this phenomenon. However, the specificity of the neural mechanisms governing this effect remain controversial. Specialist theories of imitation suggest that biological cues are maximally capable of eliciting imitative facilitation. Generalist models, on the other hand, posit a broader role for the MNS in linking visual stimuli with appropriate responses. In the present study, we investigated the validity of these two theoretical approaches by disrupting the left and right inferior frontal gyrus (IFG) during the preparation of congruent (imitative) and incongruent (complementary) actions cued by either biological (hand) or non-biological (static dot) stimuli. Delivery of TMS over IFG abolished imitative response facilitation. Critically, this effect was identical whether actions were cued by biological or non-biological stimuli. This finding argues against theories of imitation in which biological stimuli are treated preferentially and stresses the notion of the IFG as a vital center of general perception-action coupling in the human brain.